Care Services within the Elderly Support System from the Perspective of the Polish Red Cross - Rynkowska, Dorota (European Journal of Sustainable Development, 2019)
Society ageing, which results in many changes both within the social and cultural spheres, is a multi-aspect demographic process. Its basic determinants are mortality and reproduction rates, which are affected by social, economic, engineering and civilisation changes. The changes are related, among other things, with ageing of the population with chronic and geriatric diseases (B??dowski 2002). The natural consequence of ageing and the co-existing chronic diseases include the growing dependence and demand for care services among the seniors. As a result the population structure changes, care services are still at their development stage and the demand for the services has been increasing. The role of local-government and non-government entities in the area of support, aid and care services for the elderly has been gradually growing. The purpose of the article is to present the forms and scope of the care services for the seniors from the perspective of the Polish Red Cross support activities. Keywords: seniors, care, support, care services, Polish Red Cross